2016
DOI: 10.1161/circoutcomes.115.002312
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Short- and Long-Term Outcomes Among Older Patients With ST-Elevation Versus Non–ST-Elevation Myocardial Infarction With Angiographically Proven Coronary Artery Disease

Abstract: O utcomes among patients presenting with ST-segmentelevation myocardial infarction (STEMI) and non-STsegment-elevation myocardial infarction (NSTEMI) have improved markedly because of a combination of rapid recognition of the myocardial infarction (MI) event, early invasive management with revascularization, and aggressive secondary prevention treatment strategies. Previous studies have demonstrated differential short-and long-term mortality risks by MI classification (STEMI versus NSTEMI).1-4 Although patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 35 publications
5
39
1
1
Order By: Relevance
“…Figure 6 show 42% of patients with NSTEMI (non ST-Segment elevation myocardial infarction and unstable angina) and 28% of patients with STEMI were ended with early percutaneous coronary angiography (PCI) in the cardiac center. This result is differ from other study which revealed that the PCI was more common in STEMI patients compared with NSTEMI patients who had either coronary artery bypass grafting or medical management [44]. Figure 7 show that 11 patients with ACS those found to be have impaired glucose tolerance (IGT) were died during the first week of presentation in comparison with 2 patients with normal sugar state were died in that period of presentation with highly statistically significant value (P value<0.0001) which similar to a study, Prashanth Panduranga.…”
Section: Discussioncontrasting
confidence: 99%
“…Figure 6 show 42% of patients with NSTEMI (non ST-Segment elevation myocardial infarction and unstable angina) and 28% of patients with STEMI were ended with early percutaneous coronary angiography (PCI) in the cardiac center. This result is differ from other study which revealed that the PCI was more common in STEMI patients compared with NSTEMI patients who had either coronary artery bypass grafting or medical management [44]. Figure 7 show that 11 patients with ACS those found to be have impaired glucose tolerance (IGT) were died during the first week of presentation in comparison with 2 patients with normal sugar state were died in that period of presentation with highly statistically significant value (P value<0.0001) which similar to a study, Prashanth Panduranga.…”
Section: Discussioncontrasting
confidence: 99%
“…[1][2][3][4] Although both patients with NSTEMI and ST-segment elevation myocardial infarction (STEMI) are at a high risk of recurrent cardiovascular events, patients with NSTEMI have higher long-term mortality and cardiovascular risk than those with STEMI. [5][6][7][8] Furthermore, the proportion of patients with acute myocardial infarction (MI) who have NSTEMI is increasing relative to those with STEMI. [9][10][11] Results from the French Registry of Acute ST-Elevation or Non-ST-Elevation Myocardial Infarction (FAST-MI) and the Swedish Websystem for Enhancement and Development of Evidence-based care in Heart disease Evaluated According to Recommended Therapies (SWEDEHEART) registry showed that the 6-month and 1-year mortality of patients with STEMI or NSTEMI have generally decreased since 1995.…”
Section: Disease Burden Of Non-st-segment Elevation Myocardial Infamentioning
confidence: 99%
“…Despite the above recommendations and findings, patients with NSTEMI often receive less aggressive secondary prevention treatment than patients with STEMI. 8,28 Moreover, patients who have the highest ischemic risk often receive the least aggressive treatment, including both invasive and medical management; a phenomenon that has been termed the "treatment-risk paradox." [29][30][31][32] Suboptimal treatment of patients with multiple ischemic risk factors was highlighted in the Pattern of Repeat Cardiovascular Events…”
Section: Suboptimal Treatment Of Patients With Nstemimentioning
confidence: 99%
See 1 more Smart Citation
“…MI prevalence is almost twice as high for men than for women (4% vs 2.3%) in the United States, with the average age at initial MI slightly higher in women than in men (72.0 years vs 65.6 years) [3]. Patients with NSTEMI are generally older with a higher burden of disease and comorbidities, a level of clinical complexity necessitating effective transition of care management [8]. Reports indicate that two-thirds of MI are NSTEMI [9] with the risk of recurrent CV events being higher in patients with NSTEMI than in those with STEMI [8].…”
Section: Introductionmentioning
confidence: 99%